Combination of XOR Binary Algorithm and Steganography Using Least Significant Bit (LSB) Method for Data Security - Tetik, Yulius Nahak; Neno, Friden Elefri; Ariyus, Dony (Compiler, 2019)
Along with the development of technology and information today, data security is a problem that needs to be done to maintain the confidentiality of data or information both personally and within an organization. Cryptography is one of the sciences or arts that learns about how to secure data or information from irresponsible parties who want to destroy important data in the form of text and image files. This research, data security technique uses two algorithms, namely steganography to enter text in image media using LSB (Least Significant Bit) method and Binary XOR used to convert messages to binary with XOR keywords and generate pixel values of messages from 8 bits of images with LSB (Least Significant Bit). After encrypted the image will be sent to the user, and to view the original data, the user must decrypt the data with the message key and retrieve the LSB (Least Significant Bit) value, from the encrypted image.